Pengembangan Stadiometer Sebagai Alat Ukur Tinggi Badan Dan Tinggi Lutut - Sulistyawati, S (Jurnal Pengelolaan Laboratorium Pendidikan, 2019)
Anthropometric measurement aims to determine the conditions of growth and nutritional status. Linear growth can be known through height measurement. Height measurement often used microtoise which has several requirements such as requires a wall, flat place, and when installing it requires precision in pulling the tool right up to 200 cm to ensure an accurate measurement. A more practical height measuring instrument called stadiometer was made in study as a measuring instrument for height and also can be used to measure knee height. Material used aluminum to make the tool lighter, practical, and easy to carry. Validity test of tool was conducted by using stadiometer Seca 217. Height measurement was performed on 75 subjects in 7th semester students (academic year of 2015/2016) at Faculty of Public Health, University of Diponegoro Semarang. Data were analyzed by using paired t-test at significance level of 0.05 and obtained p=0.173. It was concluded that there was no significant difference in measurement results between simple stadiometer tool (the design results) and stadiometer Seca 217, so simple stadiometer tool was valid to use as height measurement tool. Keywords: stadiometer, measuring instrument, height, knee height